2022
DOI: 10.3390/w14193050
|View full text |Cite
|
Sign up to set email alerts
|

Water Requirement of Solar Greenhouse Tomatoes with Drip Irrigation under Mulch in the Southwest of the Taklimakan Desert

Abstract: Understanding crop water requirements is important for establishing irrigation schedules, and improving water use efficiency (WUE), crop yield and crop quality. In order to reveal the optimal water requirement of tomatoes in various growth stages, the responses of the water requirement, crop coefficient, fruit yield and quality of tomato to different irrigation levels were studied in a solar greenhouse in Hetian, Southwestern Taklimakan Desert, China from August 2019 to June 2020. The medium irrigation quota (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…According to the TA values obtained for the treatments, the effect of irrigation level, vermicompost doses and irrigation level x vermicompost interaction on TA was statistically significant (p < 0.01). According to research, TA decreases as irrigation level increases [46,55]. In that study, increasing irrigation levels decreased TA values, while increasing VC doses increased TA values.…”
Section: Quality Parameters Of the Tomatoesmentioning
confidence: 61%
See 1 more Smart Citation
“…According to the TA values obtained for the treatments, the effect of irrigation level, vermicompost doses and irrigation level x vermicompost interaction on TA was statistically significant (p < 0.01). According to research, TA decreases as irrigation level increases [46,55]. In that study, increasing irrigation levels decreased TA values, while increasing VC doses increased TA values.…”
Section: Quality Parameters Of the Tomatoesmentioning
confidence: 61%
“…The effects of irrigation level, VC doses and irrigation level × VC interactions on TSS were statistically significant (p < 0.01). Researchers have found the highest TSS in tomatoes at different irrigation levels, where water limitation is highest [31,55]. Siingh et al [45] found the TSS value to be 4.3 • Brix in 3-day intermittent irrigation application and 4.9 • Brix in 5 t ha −1 VC + 3-day intermittent irrigation application.…”
Section: Quality Parameters Of the Tomatoesmentioning
confidence: 99%
“…Lovelli et al [10] determined fruit TA values between 0.26 and 0.40 for different irrigation levels and reported that the difference between TA values was insignificant. Hong et al [47] reported that for different irrigation levels (60%, 80%, 100%, 120%, and 140%) the tomato fruit TA in the two seasons (Autumn-Winter and Winter-Spring) between 0.41 and 0.56. In the study, TA content increased at first and then decreased with the increase in irrigation.…”
Section: Pomological Properties Of the Tomatoesmentioning
confidence: 99%
“…In the study, the difference in TSS values between irrigation levels was statistically significant (p < 0.01). Researchers found fruit TSS values for different irrigation levels Lovelli et al [10] 5.57-7.03 in tomato, Colimba-Limaico et al [12] 3.71-4.32 in tomato, Tarı and Sapmaz [11] 4.53-5.53 in tomato, Hong et al [47] 4.21-6.10 in tomato, Ünlükara et al [36] determined it to be 5.04-6.55 in pepper, and Çolak et al [1] determined it to be 4.38-4.68 in eggplant. They also reported that the difference between TA values was significant.…”
Section: Pomological Properties Of the Tomatoesmentioning
confidence: 99%
See 1 more Smart Citation